Biological Management of Wilt in Pigeonpea Caused by Fusarium oxysporum f. sp. udum (Journal of Plant Disease Sciences, 2025)
Pigeonpea (Cajanus cajan L. Millspaugh) is a highly significant legume crop in India, serving as a crucial source of protein. However, the crop is susceptible to a wide array of pathogens, with over 100 known diseases affecting it. Among them, wilt caused by Fusarium oxysporum f. sp. udum is one of the most devastating.An in vitro experiment was conducted to evaluate eco-friendly management strategies against pigeonpea wilt. The study assessed the efficacy of eight bioagents (six fungal and two bacterial) and eight phytoextracts. Among the bioagents, the local strain of Trichoderma asperellum exhibited the highest mycelial growth inhibition (90.26%). Among the phytoextracts, neem demonstrated the highest inhibition at 10% and 20% concentrations (69.56% and 85.11%, respectively), followed by garlic (67.26% and 84%, respectively).Pigeonpea is known for its ability to restore soil fertility by fixing atmospheric nitrogen, enhancing phosphorus availability, and improving soil properties. It is the second most important pulse crop after chickpea in India, particularly in rainfed agriculture. Despite its significance, pigeonpea suffers from several economically important diseases, including sterility mosaic, Fusarium wilt, Phytophthora blight, Macrophomina root rot, Alternaria blight, stem canker, and powdery mildew.In India, wilt incidence ranges from 10% to 60% (Nene et al., 1996), with potential yield losses reaching up to 100% in susceptible cultivars (Pande et al., 2013). In Maharashtra, pigeonpea is primarily grown as a kharif crop on marginal lands by resource-poor farmers due to its resilience against water and nutrient stress. In 2021-22, Maharashtra recorded the highest area (14.18 lakh ha), production (16.49 lakh tonnes), and productivity (1163 kg/ha) for pigeonpea.
Keywords: Bioagents; Fusarium udum; Pigeonpea; Wilt; Phytoextracts